A case report of painless type A aortic dissection with intermittent convulsive syncope as initial presentation. Issue 17 (April 2017) - Chen, Chun-Hsien; Liu, Kuan-Ting
Abstract: Rationale: The initial presenting symptoms and signs of acute aortic dissection are so diverse that it makes early and accurate diagnosis arduous. Painless and convulsive syncope due to cardiac arrhythmia were not typical presentations of acute aortic dissection. Patient concerns: A 61-year-old male presenting with transient consciousness loss and suspected seizure attack was sent to emergency room (ER) by ambulance. Consciousness loss accompanying with upward gaze and limb convulsion was noted in ER, and electrocardiogram monitor recorded a transient cardiac asystole then spontaneous recovery of sinus rhythm. Diagnoses: Chest X-ray revealed widening of the mediastinum. Subsequently, contrast-enhanced chest computed tomography demonstrated Stanford type A aortic dissection. Lessons: To the authors' knowledge, this is the first reported case that cardiac asystole may be related to painless type A aortic dissection and then leading to convulsive syncope as presenting symptoms.